Book review: Rethinking the Law School: Education, Outreach, Research and Governance. Edited by Carel Stolker, Cambridge University Press, Cambridge. (January 2019) - Moulik, Ishani
Rethinking the Law School: Education, Outreach, Research and Governance. Edited by Carel Stolker, Cambridge University Press, Cambridge, 2014, 472 Pp., hb, £75.00. ISBN-13: 978-1107073890 ISBN-10: 978-1107073890